Becoming an endangered species? The future viability of Australian automotive manufacturing. (1st January 2011) - Wright, Chris F.; Clibborn, Stephen; Lansbury, Russell D.
In recent decades, successive governments have reduced tariff protection and encouraged the Australian automotive industry to become more internationally competitive. The future of automotive manufacturing now rests largely on decisions made by the three remaining global parent companies: General Motors, Ford and Toyota. Despite extensive structural reforms of the industry to make it more internationally competitive, its future remains uncertain, particularly in the aftermath of the global financial crisis.